Responses of Plant Growth and Lettuce Yields to the Application of Oyster Mushroom Baglog Waste Compost - Akhmad Gazali; Akhmad Rizali; Akbar (PT FORMOSA CENDEKIA GLOBAL, 2022)
Seeing the potential and efficacy of lettuce causes the demand for lettuce to increase. Lettuce cultivation using planting media that can be utilized is oyster mushroom baglog waste. This study aims to determine the effect of applying oyster mushroom baglog waste compost on the growth and yield of lettuce plants, to determine the best dose of oyster mushroom baglog waste compost on the growth and yield of lettuce plants. The design used was a 1-factor Completely Randomized Design (CRD) consisting of 4 treatment levels, namely A0 (control), A1 (400 g), A2 (500 g) and A3 (600 g). With 5 repetitions, there are 20 experimental units. Parameters observed in this study were plant height, number of leaves, leaf width and fresh weight of lettuce. The results showed that the application of oyster mushroom baglog waste compost had an effect on the growth and yield of lettuce. The best dose treatment for the growth and yield of lettuce is A3.